The Cornish Knitting Pattern Series film charts. Issue 1 (1st August 2019) - Nightingale, Jennifer
This visual essay appraises the film charts (shooting diagrams) used in the production of The Cornish Knitting Pattern Series in 2016. The film charts are a surprising key element arising from this period of film practice, being as they were a pragmatic part of the preproduction planning. However, through analysis of my films after production the charts have become a major source of visual thinking, notation, documentation and a significant aid to reflection on the work carried out. The Cornish Knitting Pattern Series is a collection of 16mm animation landscape films that use a single frame production technique to translate Guernsey knitting patterns into film, and in doing so set up a structural relationship between that of a knitted stitch and a frame of film – drawing out analogies between both forms of production. In this visual essay the charts' roles will be considered in the translation of the Guernsey knitting patterns in terms of preproduction visualization of the knitting patterns; notation documentation during the pro-filmic event; and retrospectively as a record of processes and production. To do it will illuminate the film practice relationship to mistakes, and the location as the editing system process that is a key aspect of the film series processes – wherein gesture, landscape and film are 'knitted together' in the film as a material object.